Subcutaneous Fat Necrosis of the Newborn: A Case Report of a Term Infant Presenting with Malaise and Fever at Age of 9 Weeks - Ayuk Adaeze Chikaodinaka; Anikene Chukwuemeka Jude (Hindawi Limited, 2015)
Background. Subcutaneous fat necrosis (SFN) is a rare, temporary, self-limited pathology affecting adipose tissue of full-term or postmature neonates. It is a rare entity especially in Nigeria and usually occurs in the first weeks following a complicated delivery. Because it is not very common, diagnosis is easily missed. It may resolve spontaneously without sequelae but patients need to be followed up because of development of late complications especially hypercalcemia. We report a case of SFN of the newborn noted within one week of birth and highlight the need for proper prompt diagnosis and the need for follow-up to assess possible complications.